The dynamics of beech forests stands above-ground phytomass depending on their assessments indexes in the prevailing site types of Polonynsky Range of the Ukrainian Carpathians - Heorhiy Hrynyk; Andriy Zadorozhnyy (Наукові праці Лісівничої академії наук України, 2018)
In connection with differences in a height and development in the different site types the features of structural components forming of above-ground phytomass in the most prevailing site types are considered and their formalization is carried out on the basis of regressive analysis. Object of the study – beech forests stands in the prevailing site types of Polo-nynsky Range of the Ukrainian Carpathians. The research aim is to design dependence of above-ground phytomass of beech forests stands from their assessments indexes. The authors used research data obtained in the result of setting 36 temporary trial plots on the territory of Polonynsky range of the Ukrainian Carpathians in order to study the dynamics of above-ground components of above-ground phytomass of beech forets stands. Trial areas are stopped up on operating requirements, and the evaluation of closeness of components of above-ground phytomass of broadleaved forest stand is studied ed followed on methodology of Prof. P.I. Lakyda. To assess beech stands phytomass it is used the value of material density in the absolutely dry state. A general tendency for studied site types consists in the increase of tree trunk phytomass with the increase of mean values of trunk height and trunk diameter . In the moist mixed broadleaved forest (C3) conditions the values of index change from 10.5-16.8 the-1 to 318-331 the-1, and in moist broadleaved forest (D3) conditions an increase takes place at the analogical values of middle high of from 9.9-16.2 the-1 to 314-327 the-1. A difference in the values of wood trunk phytomass to diminishes with the increase of mean values of trunk height and trunk diameter: from 3.7-5.4% to 1.2-1.6%. The values of trunk bark phytomass grow from 1.6-1.7 the-1 to 15.0-15.1 the-1 in C3 conditions, and from 1.4-1.6 the-1 to 14.5-14.7 the-1 in D3 conditions. For wood branches phytomass characteristic is an increase of difference with the increase of assessments indexes: in C3 conditions of value are higher and prevail analogical idexes in D3 conditions. At relative stocking of 0.7 a bark branches phytomass in C3 conditions grows from 0.62-0.64 the-1 to 4.26-4,27 the-1, and in D 3 conditions at the analogical values of middle high – from 0.60-62 to 4.13-4.14 the-1. Unlike wood branches phytomass of bark branches phytomass in the investigated site types are differs not substantially. The values of leaves phytomass in C3 conditions grow from 1.09-1.24 the-1 to 13.6-16.8 the-1 and in D 3 conditions – from 1.09-1.24 to 13.1-13.2 the-1. The least difference between the values of leaves phytomass of beech forests stands is observed in sapling stands. The increase of values of general above-ground phytomass is traced in C3 conditions from 18.7-26.8 the-1 to 415-438 the-1, and in D3 conditions – from 17.7-25.6 the-1 to 412-426 the-1. The part of difference between the values of general above-ground phytomass is in limits degrees of height trunk diminishes with the increase of middle trunk diameter. The worked out models of dependences adequately describe empiric material with the high level of approximation and characterized by sufficient statistical authenticity. On the basis of models equalizations the complex of tables of the investigated components of above-ground phytomass estimation it is worked out in absolutely dry state.